Vocal activity patterns of Malaysian Eared-Nightjar (Lyncornis temminckii) in lowland forests in Peninsular Malaysia - Chong, Leong Puan; Muhammad Adam Mah, Amera Natasha Mah; Zakaria, Mohamed; Abdul Rahim, Al-kautsar Hidayanto (Forestry Department of Peninsular Malaysia, 2024)
Malaysian Eared-nightjar (Lyncornis temminckii) is one of the five resident nightjar species found in Malaysia, which is elusive yet easily detected by vocalizations. This study aimed to assess the call types and the vocal activity patterns of the Malaysian Eared-nightjar during breeding and non-breeding seasons from four lowland forests in Peninsular Malaysia, namely Ayer Hitam Forest Reserve, National Botanical Garden Shah Alam, Bintang Hijau Forest Reserve, and Krau Wildlife Reserve. To collect the vocalizations, five Bioacoustic Audio Recorders were deployed in February – April 2022 to account for the breeding season while in October – December 2021 and November 2022 for the non-breeding season. The recorders were left to record for eight consecutive days in each site and season. All the nightjar’s vocalizations were retrieved and sorted into call events to visualize its diel vocal activity patterns. From a total of 10,128 recording hours, one call type of the Malaysian Eared-nightjar was recorded possibly as advertising or territorial calls uttered in flight. The nightjar vocalized mostly at dawn and dusk. In finer timescale, the nightjar started to vocalize shortly before sunset and ended after sunrise during breeding season while shortly after sunset and before sunrise during non-breeding season. Insights on the temporal vocalization may fill the knowledge gaps and help future surveys in planning appropriate survey period at times where the nightjar is most active, increasing the chances of detecting it in the field.